(untitled) (Encuentros, 2020)
Animals are essential to human civilization and most people have at some time spoken with an animal. Studies regarding animal-directed speech focus on in-play ethnography, using animals as discursive mechanisms and only focus on pets – and all are done in Anglophone countries. This study explores the apparent gap in research. In a study performed in Ibagué, Colombia, 500 people were surveyed in a self-report quantitative study to analyse how many people actually speak with animals (pets and non-pet domestic animals), how they do so and what beliefs they hold about animal-directed human speech. It was found that the majority of the population report speaking with animals and that factors such as gender, level of education, owning a pet and the pet actually exerting strong influences on how the animals are spoken. Additionally, the study highlights a set of contradictions in terms of attitude and practice – particularly in pronoun use and the social proximity enacted in social relationships with animals which are not actually reflected in the linguistic content of the discourse. The study concludes that people in regional Colombia speak to animals, not because they believe the animal understands them but, because humans understand relationships through spoken discourse and as such use linguistic discourse to create or enact a relationship with animals. Key words: pet-talk, animal-directed speech, human-animal relationships.